2019
DOI: 10.1101/748566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bidirectional crosstalk between Hypoxia-Inducible Factor and glucocorticoid signalling in zebrafish larvae

Abstract: AbstractIn the last decades in vitro studies highlighted the potential for crosstalk between Hypoxia-Inducible Factor-(HIF) and glucocorticoid-(GC) signalling pathways. However, how this interplay precisely occurs in vivo is still debated. Here, we use zebrafish larvae (Danio rerio) to elucidate how and to what degree hypoxic signalling affects the endogenous glucocorticoid pathway and Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 77 publications
4
10
0
Order By: Relevance
“…Undoubtedly, such models would help us to better understand the crosstalk between HPPs and adrenal steroid metabolism, while simultaneously serving as an essential tool to study the pathophysiology of multiple conditions associated with dramatically altered steroid hormone levels (2). Ablation of HIF1α revealed an important role for this transcription factor in steroidogenesis, which concurs with results from previous studies (20,50). However, our findings that HIF1α deletion results in the upregulation of mRNA of a vast majority of steroid-related enzymes is counterintuitive to the nature of this transcription factor (12, 51), and therefore we believe this effect is most likely indirect with potential involvement of one or more transcriptional repressors (13,52,53).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Undoubtedly, such models would help us to better understand the crosstalk between HPPs and adrenal steroid metabolism, while simultaneously serving as an essential tool to study the pathophysiology of multiple conditions associated with dramatically altered steroid hormone levels (2). Ablation of HIF1α revealed an important role for this transcription factor in steroidogenesis, which concurs with results from previous studies (20,50). However, our findings that HIF1α deletion results in the upregulation of mRNA of a vast majority of steroid-related enzymes is counterintuitive to the nature of this transcription factor (12, 51), and therefore we believe this effect is most likely indirect with potential involvement of one or more transcriptional repressors (13,52,53).…”
Section: Discussionsupporting
confidence: 92%
“…Studies on the role of HIFs in the regulation of steroidogenesis in vitro are few, apart from those in zebra fish larvae that describe differential regulation of the enzymes involved in the steroid pathway (7,18,20). However, to the best of our knowledge, there are no mouse models to study the role of HPPs in adrenal cortical cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, GRE motifs have a vital role in the cellular response to stress (64). A recent study showed that glucocorticoids promote HIF activity via multiple routes including glucocorticoid receptors (65). Collectively, it seems that both winners and losers were tolerant of oxygen deficiency and stress based on the enrichment of HRE and GRE transcription factor−binding motifs among the DEGs that were expressed in the brains of these fish.…”
Section: Genes and Molecular Events Associated With Neurophysiologicamentioning
confidence: 99%